The walled nuns of the crypt of Santissima Annunziata in Valenza (Piedmont, Italy) - Fusco, Roberta; Tesi, Chiara (Medicina Historica, 2019)
The Church of SS. Annunziata in Valenza was built in 1699, together with an underground crypt that preserves the cells in which, according to a particular type of burial practice, the nuns of the nearby cloistered convent were deposed. The hypogeum space was brought to light in the twentieth century, paving the way to the study of the ritual underlying this practice and to the anthropological study of the remains that the opening of the cells have brought to light.